The Emotional Reactivity in the Digital Era: A Systematic Review from a Lifespan Perspective - Nurul Fashliyah Thamrin; Tulus Winarsunu; Nida Hasanati (CV Projurnal Mitra Publikasi, 2025)
Digital technology has become an integral part of everyday life and may influence individuals’ emotional responses across different stages of development. This systematic review aims to examine the role of emotional reactivity within digital interaction contexts across different stages of human development. A structured review was conducted using the SPIDER framework, with articles sourced from Google Scholar between 2020 and 2025. From an initial pool of 201 records, 10 studies met the inclusion criteria after a multi-stage screening process. The findings indicate that emotional reactivity plays a dynamic and context-dependent role in digital behavior. In early childhood and adolescence, it primarily functions as a dependent variable influenced by digital exposure, such as excessive screen time and negative social media interactions, which may heighten emotional instability. In contrast, during adulthood, emotional reactivity tends to act as a relatively stable predispositional factor, functioning as a predictor or mediator of behaviors such as social media addiction, Fear of Missing Out (FOMO), phubbing, susceptibility to misinformation, and problematic online gambling. In older adults, heightened emotional reactivity is associated with increased vulnerability in digital information processing, particularly in evaluating the credibility of online content. Overall, the findings highlight a reciprocal relationship between digital environments and emotional reactivity. Interventions should extend beyond limiting screen time to strengthening emotional regulation and self-awareness across the lifespan.